Nanotherapeutic delivery of antibiotic cocktail enhances intra-macrophage killing of Mycobacterium marinum - Andrea M. Binnebose; Andrea M. Binnebose; Andrea M. Binnebose; Adam S. Mullis; Shannon L. Haughney; Balaji Narasimhan; Bryan H. Bellaire; Bryan H. Bellaire (Frontiers in Antibiotics, 2023)
Mycobacterium marinum is a waterborne pathogen responsible for tuberculosis-like infections in cold-blooded animals and is an opportunistic pathogen in humans. M. marinum is the closest genetic relative of the Mycobacterium tuberculosis complex and is a reliable surrogate for drug susceptibility testing. We synthesized and evaluated two nanoparticle (NP) formulations for compatibility with rifampicin, isoniazid, pyrazinamide, and ethambutol (PIRE), the front-line antimycobacterial drugs used in combination against active tuberculosis infections. Improved in vitro antimicrobial activity was observed with encapsulated rifampicin alone or in a cocktail of drugs formulated through co-encapsulation in amphiphilic polyanhydride NPs. Broth antimicrobial testing revealed that the encapsulation of PIRE in NP resulted in a significant increase in antimicrobial activity, with the benefit over soluble formulations at biologically relevant concentrations ranging from >10 to >3,000 fold. M. marinum-infected human macrophages treated with NP-PIRE were cleared of viable bacteria in 48 h following a single treatment, representing a >4 log reduction in colony-forming units and a >2,000-fold increase in antimicrobial activity. The amphiphilic polyanhydride nanoparticles demonstrated the ability to co-encapsulate PIRE antibiotics and enhance their antimicrobial activity against M. marinum in infected macrophages in culture and in vitro. These data suggest that polyanhydride nanoparticles are a promising nanotherapeutic for combatting Mycobacterium infections through improved intracellular targeting of encapsulated antibiotics.